Respuesta :
first find a least common denominator. in this case it will be 12 now multiply your denominator and numerator by the number you need to use in order to get 12, this will give you 6x/12+2x/12=7, now add your fractions and get 8x/12=7, now multiply 7 times 12 and get 84, now divide 84 by 8 to get 10.5, now plug in 10.5 on x to check our work, this will give you 10.5/2(which is 5.25)+10.5/6(which is 1.75) and when these 2 are added we do get 7.... this means x equal 10.5
Hope this helps
Hope this helps
(x/2) + (x/6) = 7
you need to get your x variable alone here, but you have two fractions that are adding your x's, so you have to get your common denominator to cancel them out. the common denominator here is actually 6 -- 6 goes into itself 1 time, 2 goes into 6 three times. multiply the ENTIRE equation by 6, because you must do the same thing to both sides.
(x/2)*6 + (x/6)*6 = 7*6 .... simplify
3x + x = 42 ... combine like terms
4x = 42 ... divide by 4
x = 42/4 ... simplify your fraction
x = 21/2
you need to get your x variable alone here, but you have two fractions that are adding your x's, so you have to get your common denominator to cancel them out. the common denominator here is actually 6 -- 6 goes into itself 1 time, 2 goes into 6 three times. multiply the ENTIRE equation by 6, because you must do the same thing to both sides.
(x/2)*6 + (x/6)*6 = 7*6 .... simplify
3x + x = 42 ... combine like terms
4x = 42 ... divide by 4
x = 42/4 ... simplify your fraction
x = 21/2